Biomimicry in Malaysian architecture: crafting a modular framework for sustainable design - Muhammad Danish; Mohd Noor, Mohd Zairul; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This research investigates how Malaysian architecture may use biomimicry concepts to alleviate environmental issues and advance sustainability. Notwithstanding Malaysia's dedication to sustainable development, the country's fast industrialization and urbanization have a substantial ecological influence on the architectural industry. There is a need to adopt biomimicry—a technique modelled after the structures and functions of nature—in this setting since traditional sustainable approaches are insufficient. This study develops a framework for biomimetic design criteria using semi-structured interviews with architects, precedent studies, and literature evaluation. Anticipated outcomes encompass the identification of economical and energy-efficient construction techniques that mitigate environmental effects, augment societal welfare, and foster economic expansion. By expanding the body of knowledge on biomimicry and offering useful recommendations for architects and policymakers, the project seeks to advance the academic community. This will ultimately foster innovation in sustainable architecture, aligning with Malaysia’s sustainability goals and potentially serving as a model for other regions.